USE OF INNOVATIVE TECHNOLOGIES IN THE DEVELOPMENT OF SPECIALIZED SKILLS IN BOXERS (Spectrum Journal of Innovation, Reforms and Development, 2024)
In this article, the author tried to shed light on the psychological features of feeling the gap in boxers through a new methodology. The author tried to explain the elements of feeling of distance in boxers using a device that allows measuring nine types of distance in boxers.